Prediction model for the flexural strength of steel fiber reinforced concrete beams with fiber-reinforced polymer bars under repeated loading. (15th October 2020) - Zhu, Haitang; Li, Zongze; Wen, Chengcheng; Cheng, Shengzhao; Wei, Yunxiao
Abstract: This study investigates the flexural performance of steel fiber reinforced concrete (SFRC) beams with fiber-reinforced polymer (FRP) bars under repeated loading. Fourteen beams with dimensions of 150 mm × 300 mm × 2100 mm were cast and tested via a four-point bending test. The effects of the FRP reinforcement ratio, type of reinforcement, concrete strength, steel fiber shape, and steel fiber volume fraction on the failure mode, cracking moment, skeleton curve, deflection, strength degradation, and flexural strength of the beams were investigated. The test results revealed two different failure modes for the SFRC beams reinforced with FRP bars, including compression failure and tensile failure. The flexural strength of the beams decreased as the number of load cycles increased under the same deflection. A higher FRP reinforcement ratio, concrete strength, and steel fiber volume fraction enhanced the flexural strength of the beams and decreased the deflection. Finally, the flexural strength test results were compared with several different prediction models. The ACI 440.1R-15, CSA S806-12, and GB 50608–2010 models underestimated the flexural strength of the beams, while the proposed prediction model, which based on the equivalent force block, provided more accurate prediction results.